La influencia del fuego, exposición de ladera y posición topográfica sobre la vegetación y el suelo en la zona de transición entre bosques y pastizales de las Sierras de Córdoba - Giorgis, Melisa Adriana (2013)
The effect of fire and topographic features on vegetation and soil properties in woodlands and grasslands transition in Córdoba mountains, Argentina. Under the currently context of climate change the dynamic of the transition zone between forests and grasslands has a fundamental role at both scientific level and in planning and ecosystem management. In this study, we evaluated the combined effect of fire, slope aspect and topographic position on vegetation and soil characteristics of the Córdoba Mountains in the transition zone between woodlands and grasslands. We selected four areas with different post-fire age. In each area we selected all possible combinations of slope aspects and topographic positions. In each site we performed floristic surveys and analyzed a composite sample of soil. Fire was the main factor associated with the different characteristics analyzed (physiognomy, floristic composition, soil characteristics), and separated burned from unburned sites. Slope aspect also contributed, conditioning physiognomy, floristic composition and soil characteristics. However we did not found a straight relationship between the recovery of tree cover and the time after the last fire, indicating that other factors such as geomorphology, land use history, and herbivory would also condition post-fire recovery of these systems.